Pengembangan Modul Praktikum Akuntansi Berbasis Perkebunan Kelapa Sawit pada Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi - Muhammad Sapruwan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
This research discusses how to realize the accounting practicum module based on palm oil plantation. Preparation of this practicum module intended to support quality of superior human resources from a graduate of the Polytechnic of Kelapa Sawit Citra Widya Edukasi. The object of this study on Polytechnic of Kelapa Sawit Citra Widya Edukasi, Bekasi. Currently in the polytechnic there is no Accounting Practicum Module based on palm oil plantation. The researcher wish to develop the material of accounting practicum course according to condition of requirement that happened in the field, that is in the form of development of accounting practice module based on palm oil plantation. The purpose of this research is to realize the accounting practicum module of accounting based on palm oil plantation and to know the implementation of accounting practicum module to student of Polytechnic of Kelapa Sawit Citra Widya Edukasi, and to evaluate the result of its assessment. This research uses research and development (R&D) method, by adopting the approach of ADDIE (Analysis, Design, Development, Implementation and Evaluation) by Maribe Branch. The results obtained in this study are accounting practicum module based on palm oil plantation, application of accounting practicum module and evaluation of assesment.